Fatherless in indonesia and its impact on children’s psychological development - Ashari, Yulinda (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2018)
The power of the child's personality is the result of good parenting and handling by both of parents. If one is absent, there will be an imbalance to child psychological development. The fatherless concept itself can be interpreted as the absence of a father figure in the nurturing process. Then known the "fatherless", "father absence", "father loss" or "father hunger". The fatherless issue has become an international problem, including in Indonesia. Most cases in Western countries are the absence of fathers due to unmarried fathers and mothers, it’s different with Indonesia's problems, the fathers and mothers are married, but the execution of the parenting tasks is neglected or unfulfilled. Many children have a physical father but at the same time fatherless psychologically. It seems the traditional parenting pattern in Indonesia that the role of mother is taking care of the child at home and father is working to earn a living is still believed without further meaning. Father contributes importantly to the development of the child, the experience with father will affect a child to adulthood later. Father has influences in some special areas of child development, which teaches freedom, expands children's view, firm discipline, and role models of male. It is hypothesized that fatherless will give negative impact to psychological development of children. The literature reviews is used to support the hypothesized in this paper.